Reflux pretreatment-mediated sonication: A new universal route to obtain 2D quantum dots. (January 2019) - Liu, Yang; Liang, Chenglu; Wu, Jingjie; Varma, Sreekanth J.; Nakanishi, Yusuke; Aliyan, Amir; Martí, Angel A.; Wang, Yan; Xie, Banghu; Kumar, Jitesh; Layne, Katherine; Chopra, Nitin; et al.
Graphical abstract: Abstract: Although quantum dots (QDs) based on two dimensional (2D) materials have manifested fascinating properties and promising applications in a wide range of fields, a low cost and non-tedious approach for the preparation of atomically thick 2D QDs with high yield remains elusive. Herein, for the first time, we demonstrate a reflux pretreatment-mediated sonication approach to produce a series of ultrathin 2D QDs (e.g., graphene, TiS2, MoS2, MoSe2, WSe2, NbS2, SnS2, and h-BN QDs) from their bulk counterparts. The solvent molecules, confined in the channels of layered materials during reflux, assist the delamination and fracture of 2D sheets in the process of bath sonication. The resulting 2D QDs exhibited uniform lateral size distribution of 2–7 nm and a mean thickness of 0.8–1 nm, almost identical to the monolayer thickness of layered materials. To demonstrate the unique property of these 2D QDs, the optical limiting activity was studied using open aperture z-scan technique. TiS2 QDs exhibited appreciable nonlinear optical limiting, reaching 50% by a tapered and sharp absorption at input laser fluence of 4.24 GW/cm 2 .